Unleashing the Power of Class Action Lawsuits: Redefining Justice for Insurance Policyholders in Indonesia - Haryanto, Imam; Suherman, Suherman; Sakti, Muthia; Khalilullah, Ibrahim Hanif (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
This paper explores the transformative potential of class action lawsuits in redefining justice for insurance policyholders in Indonesia. Through an in-depth examination of the legal landscape and specific cases, the study delves into the mechanisms and implications of leveraging class actions as a means of seeking justice within the insurance sector. By analyzing notable instances, such as the class action lawsuit initiated by insurance policyholders of PT Asuransi Jiwasraya and PT Asuransi Jiwa Adisarana WanaArtha, the paper scrutinizes the impact of collective legal action in addressing grievances and restoring violated rights. The research also navigates the legal provisions surrounding class actions in Indonesia, shedding light on their relevance and effectiveness in the pursuit of justice for insurance policyholders. Ultimately, this paper contributes to the ongoing discourse on legal remedies within the insurance industry, offering insights into the potential of class action lawsuits as a powerful tool for policyholders to assert their rights and demand justice in the Indonesian legal context.